Challenges of Implementing Lung Cancer Screening in a Developing Country: Results of the Second Brazilian Early Lung Cancer Screening Trial (BRELT2). (24th January 2022) - Hochhegger, Bruno; Camargo, Spencer; da Silva Teles, Gustavo Borges; Chate, Rodrigo Caruso; Szarf, Gilberto; Guimarães, Marcos Duarte; Gross, Jefferson Luiz; Barbosa, Paula Nicole Vieira Pinto; Chiarantano, Rodrigo Sampaio; Reis, Rui Manuel; Mauad, Edmundo Carvalho; Ghefter, Mario; et al.
Abstract : PURPOSE: This paper aims to present the results of a series of several Brazilian institutions that have been carrying out lung cancer screening (LCS). MATERIALS AND METHODS: This is a retrospective, cohort study, with follow-up of individuals of both sexes, with a heavy smoking history, who participated in LCS programs between December 2013 and January 2021 in six Brazilian institutions located in the states of São Paulo, Rio Grande do Sul, and Bahia. RESULTS: Three thousand four hundred seventy individuals were included, of which 59.8% were male (n = 2, 074) and 50.6% were current smokers (n = 1, 758), with 60.7 years (standard deviation 8.8 years). Lung-RADS 4 was observed in 233 (6.7%) patients. Biopsy was indicated by minimally invasive methods in 122 patients (3.5%). Two patients who demonstrated false-negative biopsies and lung cancer were diagnosed in follow-up. Diagnosis of lung cancer was observed in 74 patients (prevalence rate of 2.1%), with 52 (70.3%) in stage I or II. Granulomatous disease was found in 20 patients. There were no statistical differences in the incidence of lung cancer, biopsies, granulomatous disease, and Lung-RADS 4 nodules between public and private patients. CONCLUSION: There are still many challenges and obstacles in the implementation of LCS in developing countries; however, our multi-institutional data were possible to obtain satisfactory results in these scenarios and to achieve similar results to the main international studies. Granulomatous diseases did not increase the number of lung biopsies. The authors hope that it could stimulate the creation of organized screening programs in regions still endemic for tuberculosis and other granulomatous diseases. Abstract :